2019
DOI: 10.1093/ajcp/aqz045
|View full text |Cite
|
Sign up to set email alerts
|

Reaffirming the Value of the Autopsy

Abstract: Objectives To determine characteristic features of myocardial infarction (MI) diagnosed at autopsy and establish the incidence of discrepancy. Methods Autopsy cases at a tertiary hospital with a pathologic diagnosis of acute MI were evaluated for clinicopathologic features. Modified Goldman’s classification was used to classify discrepant cases. Results Of 52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…A recent study published earlier this year showed that type II MI, resulting from an improper myocardial oxygen supply-demand ratio, accounted for 85% of the patients with MI in this series (8). We believe that type II MI could be exacerbated in critically ill patients needing ECMO in multiple ways.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…A recent study published earlier this year showed that type II MI, resulting from an improper myocardial oxygen supply-demand ratio, accounted for 85% of the patients with MI in this series (8). We believe that type II MI could be exacerbated in critically ill patients needing ECMO in multiple ways.…”
mentioning
confidence: 52%
“…Major discrepancy rates for MI range between 13% and 28.3% of all autopsy cases outside the ICU setting (8).…”
mentioning
confidence: 99%
“…Great efforts should be made in the future to improve this virtuous practice, and general practitioners need to be involved by relatives towards an awareness of the importance of autopsy [62,63]. The number of autopsies requested by families of the deceased is still low, and the promotion is needed in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…ІМ часто зустрічається під час патологоанатомічних розтинів [11,12], й діагностика може бути складною щодо виявлення різних типів ураження міокарда, особливо за відсутності гострої коронарної оклюзії. Належний посмертний діагноз, встановлення безпосередньої причини смерті вимагає сучасних знань про гострий ІМ та правильної інтерпретації посмертних змін з урахуванням клінічного епікризу.…”
Section: вступunclassified